Effect of health insurance in India: A randomized controlled trial - Anup Malani; Phoebe Holtzman; Kosuke Imai; Cynthia Kinnan; Morgen Miller; Shailender Swaminathan; Alessandra Voena; Bartosz Woda; Gabriella Conti (Institute for Fiscal Studies (IFS), 2021)
We report on a large randomized controlled trial of hospital insurance for above-poverty-line Indian households. Households were assigned to free insurance, sale of insurance, sale plus cash transfer, or control. To estimate spillovers, the fraction of households offered insurance varied across villages. The opportunity to purchase insurance led to 59.91% uptake and access to free insurance to 78.71% uptake. Access increased insurance utilization. Positive spillover effects on utilization suggest learning from peers. Many beneficiaries were unable to use insurance, demonstrating hurdles to expanding access via insurance. Across a range of health measures, we estimate no significant impacts on health.
Keywords: 330; Gesetzliche Krankenversicherung; Nachfrage; Gesundheitskosten; Gesundheit; Indien